Isolation and Diagnosis of Staphylococcus spp. using VITEK-2 System from Nasal and Ear of Healthy Carriers - Sddiq Ghani Al-Muhanna (Journal of Global Pharma Technology, 2019)
One hundred of nasal and ear swabs were collected from healthy students of Babylon University who not suffering from any upper respiratory tract infection and have not received any antibiotics from the period of two. All they were cultured on suitable media .The positivity of culturing on Mannitol salt agar (selective media for Staphylococci) was 20% distributed as 14% for nasal swabs and 6% for ear swabs. When Biochemical and Serological tests were used for identifying Staphylococcus species, the results showed that 45% of these isolates were Coagulase positive while 55% were Coagulase negative .Staphylococcus species were identified by using VITEK-2: Staphylococcus aureus 45%, S. epidermidis 20%, S.capitis sub.capitis20% and S.cohni. Sub. cohni 10% .Antibiotic sensitivity test for Staphylococcus isolates showed sensitivity for ciprofloxacin to all isolates while appeared resistant to Nalidixic acid, Kanamycin and Gentamycine, most of Staphylococcus aureus isolates were resisted to Methicillin antibiotic.